Entrainment and Transport of Well‐Sorted and Mixed Sediment Under Wave Motion. Issue 8 (23rd August 2022) - Rafati, Yashar; Hsu, Tian‐Jian; Calantoni, Joseph; Puleo, Jack
Abstract: Entrainment and suspension of sediment particles with the size distribution similar to a range of natural sands were simulated with a focus on the vertical size sorting and transport dynamics in response to different wave conditions. The simulations were performed using a two‐phase Eulerian‐Lagrangian model by combining the LIGGGHTS discrete element method solver for sediment and SedFoam solver for the fluid phase. The model was first validated for a range of sand grain sizes from 0.21 to 0.97 mm having well‐sorted and mixed (bimodal) size distributions using laboratory oscillatory flow data. Three sediment bed configurations were studied under a wide range of velocity‐skewed waves with different wave intensity and skewness. It was found that the bimodal distribution having only 30% of coarse fraction and 70% of medium fraction responds similar to a well‐sorted coarse sand configuration. Sediment fluxes of the bimodal distribution were slightly higher than those of well‐sorted coarse sand because of the pronounced inverse grading in the bimodal distribution. Furthermore, for the bimodal distribution the medium fraction acted as a relatively smooth foundation underneath the coarse fraction which facilitated the mobilization of the coarser particles. Under high energy wave conditions, the smoothing feature was exacerbated and further caused the formation of plug flow where a thick layer of intense sediment flux was observed. Model results also showed that under high skewness waves, phase‐lag effect occurred in well‐sorted medium sand which caused lower net onshore sediment transport rates but the effect was significantly reduced for mixed sediments. Plain Language Summary: Sediment transport driven by shoreward propagating waves depends on the sediment particle size. Generally, coarse particles (greater than 0.5 mm diameter) respond directly to the wave motion due to being entrained and transported near the bed with faster settling whereas medium particles (smaller than 0.3 mm diameter) do not respond directly to the flow field due to sediment entrainment away from the bed and slower settling. Natural sediment in coastal zones has a variety of sediment sizes often classified as well‐sorted (nearly uniform sizes) or poorly sorted (mixed sediment sizes). The response of well‐sorted sediment particles can be characterized and predicted with a representative sediment diameter. However, the response of mixed sediment depends on the size fractions and the interaction of different size fractions with each other and with the flow field. Well‐sorted and mixed sediment particles were simulated using a computational model with conditions representative of normal and storm waves. Mixed sediment with only 30% of the coarse fraction (70% of the medium fraction) responded similar to the well‐sorted coarse sediment with slightly higher sediment fluxes due to the inverse vertical sorting (upward coarsening). Additionally, the medium particles serve as a smooth bed underneath coarse particles enhancing sediment entrainment. Key Points: Transport rates of mixed sand with bimodal distribution are similar to those of well‐sorted coarse sand Plug flow formation depends on the particle size distribution and occurs for the bimodal distribution Phase lags in sediment entrainment and sediment settling are important for predicting net transport rates